Analisis Motif dan Kepentingan Amerika Serikat dalam Penanganan dan Pencegahan Kejahatan Trafficking in Persons (TIP) di Indonesia - Ilyas, Maulana Muhammad; Susiatiningsih, Hermini; Paramasatya, Satwika (Journal of International Relations, 2018)
Trafficking in Persons (TIP) is a form of modern-day slavery which seizes the human rights and freedom of its victims. The alarming situation of this transnational crime development has led the world leaders to realize the necessity of a jointly agreed international instrument to prosecute and prevent this notorious crime. Then, the Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children UNTOC was established in 2000. In 2001, the United States emerged as an advocate of Palermo Protocol towards entire countries in the world. The U.S. has promoted compliance to the TIP Protocol through an annual TIP report, followed by unilaterally exercised rewards and punishments. The U.S. always reiterates that her active role in the global TIP prosecution and prevention is intended to uphold human rights and freedom values. Nonetheless, the U.S. sincerity has been questioned by some parties, criticized for its self-interest and political tendency. This thesis will reveal the motive/reason behind the U.S. active role in Indonesia’s TIP prevention, prosecution, dan protection through application of rational theory of International Relations. This thesis applies qualitative research method to gain perceptivity of reason, opinion, and motive underlying actor’s behavior. The conclusion of this thesis is that the U.S. takes active role in Indonesia’s TIP prevention, prosecution, and protection to gain her self-interest in maintaining safe migration. Her motive is to contain terrorism Indonesia.